KINERJA ROLE ONLINE SYSTEM TICKETING RAHARJA (ROOSTER) DALAM MENUNJANG SISTEM PELAYANAN IDUHELP! PADA PERGURUAN TINGGI - Untung Rahardja; Meta Amalya Dewi; Citra Destianty (CCIT Journal, 2014)
The advancement of information technology has positive impacts on life, especially in the service system. Current university has implemented a system information, applicable campuswide known as iDuHelp service system. However, problems are identified in the iDuHelp service system, which will be further described in detail. The problem is then resolved with the support of the performance from ROOSTER (Role Online System Ticketing Raharja), by providing unique ticket numbers which will be transferred to the relevant parties in order to provide accurate information. Many related methods of this study, including the methods of iLearning, also the road map of the study and mindmapping, arefurther described in detail and will eventually produce clearer research outcomes. The method of analysis is also done through three stages, namely the identification of information needed, identification of system requirements, and eventually the survey on the current system. Described in this article are the problems that arise and the solution to the problem under study. There is also a flowchart workflow. In the prototype implementation of iDuHelp, will be shown the system performance of ROOSTER and the listing program. It can be concluded that the performance of ROOSTER can maximize the service system iDuHelp on higher education platform .